2017
DOI: 10.1111/plb.12669
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the geographic dichotomy hypothesis with cacti in South America

Abstract: The Cactaceae is one of the most conspicuous and ecologically important plant families in the world. Its species may have specialist or generalist pollination systems that show geographic patterns, which are synthesised in the Geographic Dichotomy Hypothesis. Here, we assess this hypothesis in five countries in both tropical and extratropical regions, evaluating the pollinator visitation rate and pollinator identity and abundance. We calculate the Shannon diversity index (H') and evenness (J) and evaluate diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 19 publications
1
10
0
Order By: Relevance
“…The latter seem to be common in species inhabiting extratropical latitudes, whereas the specialized systems are characteristic of tropical species, supporting the geographic dichotomy hypothesis put forward by Fleming et al (1996) and Valiente-Banuet et al (1996). Different studies have confirmed this pattern for species occupying tropical latitudes in the northern hemisphere (Fleming 1993;Nassar et al 1997;Valiente-Banuet et al 1997a;Ibarra-Cerdeña et al 2005;Munguía-Rosas et al 2009;Arzabe et al 2017); however, research on the pollination systems in Cactaceae inhabiting tropical and subtropical regions in the southern hemisphere suggests that dependence on pollinators is not as strong, bringing about mixed mating systems (e.g. Corryocactus melanotrichus (K.…”
Section: Introductionsupporting
confidence: 60%
See 1 more Smart Citation
“…The latter seem to be common in species inhabiting extratropical latitudes, whereas the specialized systems are characteristic of tropical species, supporting the geographic dichotomy hypothesis put forward by Fleming et al (1996) and Valiente-Banuet et al (1996). Different studies have confirmed this pattern for species occupying tropical latitudes in the northern hemisphere (Fleming 1993;Nassar et al 1997;Valiente-Banuet et al 1997a;Ibarra-Cerdeña et al 2005;Munguía-Rosas et al 2009;Arzabe et al 2017); however, research on the pollination systems in Cactaceae inhabiting tropical and subtropical regions in the southern hemisphere suggests that dependence on pollinators is not as strong, bringing about mixed mating systems (e.g. Corryocactus melanotrichus (K.…”
Section: Introductionsupporting
confidence: 60%
“…; Arzabe et al . ); however, research on the pollination systems in Cactaceae inhabiting tropical and subtropical regions in the southern hemisphere suggests that dependence on pollinators is not as strong, bringing about mixed mating systems (e.g. Corryocactus melanotrichus (K.…”
Section: Introductionmentioning
confidence: 99%
“…A recent evaluation of the ‘geographical dichotomy hypothesis’ carried out recently for South American cacti by Arzabe et al . (2018) stated that pollination systems are more specialized in the tropics. However, their definition of specialization was unclear, and their results were limited by the low number of taxa studied: a set of species of the same genus in the extra‐tropics, and species from five different genera in the tropics.…”
Section: Discussionmentioning
confidence: 99%
“…As other studies point out, the answer to this question depends on the concept of specialization that is being used, as well as the methodological approach used to test the pattern (Ollerton & Cranmer, 2002;Dalsgaard et al, 2017). A recent evaluation of the 'geographical dichotomy hypothesis' carried out recently for South American cacti by Arzabe et al (2018) stated that pollination systems are more specialized in the tropics. However, their definition of specialization was unclear, and their results were limited by the low number of taxa studied: a set of species of the same genus in the extra-tropics, and species from five different genera in the tropics.…”
Section: Discussionmentioning
confidence: 99%
“…Although several studies have supported the geographic dichotomy hypothesis in columnar cacti, most of them were conducted in the northern hemisphere and little information is available on the pollination systems of cacti in the southern hemisphere (Arzabe et al . 2018).…”
Section: Introductionmentioning
confidence: 99%